Two Lip Carcinomas following Allogeneic Hematopoietic Stem Cell Transplantation: A Case Report and Literature Review - Nouha Dammak; Latifa Berrezouga; Manel Njima; Ines Lahouel; Mehdi Khemiss; Mohamed Ben Khelifa (Hindawi Limited, 2021)
Background. Secondary solid cancers are severe complications in patients who have undergone allogeneic hematopoietic stem cell transplantation (AHSCT) for malignant and nonmalignant lymphohematopoietic diseases. Objective. The aim of this work was to report a case of two lip carcinomas following AHSCT and to warn doctors about the importance of regular check-ups of patients who have received HSCT. Observation. A 57-year-old man was referred by the dermatology department for the management of exophytic budding lesions on the lower lip evolving since 5 months. The patient was in complete remission following allogeneic bone marrow transplantation for acute myeloid leukemia since five years. Clinical and histological findings confirmed the diagnosis of a squamous cell carcinoma of the two lesions. Conclusion. It is of paramount importance to seek an oral squamous cell carcinoma in the presence of persistent lesions in HSCT recipients.